Faktor Faktor Yang Mempengaruhi Struktur Modal Pada Industri Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Budi Febrian (Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to determine the effect of firm size, asset structure, and profitability on capital structure (a case study on consumption manufacturing companies listed on the Indonesia Stock Exchange in 2018 – 2020). The data used in this study is secondary data in the form of financial statements. The research sample was taken using the purposive sampling method and based on predetermined criteria, a sample of 26 manufacturing companies in the consumption sector listed on the Indonesia Stock Exchange in 2018 - 2020. The analytical method used was quantitative analysis using the Econometric Views 9 (Eviews) program application tool. 9) . The results of this study indicate that company size partially has no positive and significant effect on capital structure, and shows a probability value of 0.08 greater than 0.05 or (0.08 > 0.05), asset structure partially has no positive and significant effect. on Capital Structure, and shows a probability value of 0.00 less than 0.05 or (0.00 < 0.05).